2012
DOI: 10.4049/jimmunol.1100903
|View full text |Cite
|
Sign up to set email alerts
|

Three Novel Acetylation Sites in the Foxp3 Transcription Factor Regulate the Suppressive Activity of Regulatory T Cells

Abstract: The Foxp3 transcription factor is the master regulator of regulatory T cell (Treg) differentiation and function. Its activity is regulated by reversible acetylation. Using mass spectrometry of immunoprecipitated proteins, we identify three novel acetylation sites in murine Foxp3 (K31, K262, and K267) and the corresponding sites in human FoxP3 proteins. Newly raised modification-specific antibodies against acetylated K31 and K267 confirm acetylation of these residues in murine Tregs. Mutant Foxp3 proteins carry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
125
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(129 citation statements)
references
References 52 publications
(74 reference statements)
4
125
0
Order By: Relevance
“…Ubiquitylation of FOXP3, RORγt and T-bet controls transcription factor stability, and dysregulation of the ubiquitylating or de-ubiquitylating enzymes can induce phenotypic plasticity in these cells [183][184][185] . Blocking the activity of sirtuin 1 preserves FOXP3 acetylation, enhancing FOXP3 stability and T Reg cell function 186,187 , whereas inhibition of sirtuin 1 increases RORγt acety lation in T H 17 cells, which impedes RORγt activity 188 , thus creating another therapeutically exploitable dichotomy between inflammatory and regulatory cells.…”
Section: Gene Expression Regulationmentioning
confidence: 99%
“…Ubiquitylation of FOXP3, RORγt and T-bet controls transcription factor stability, and dysregulation of the ubiquitylating or de-ubiquitylating enzymes can induce phenotypic plasticity in these cells [183][184][185] . Blocking the activity of sirtuin 1 preserves FOXP3 acetylation, enhancing FOXP3 stability and T Reg cell function 186,187 , whereas inhibition of sirtuin 1 increases RORγt acety lation in T H 17 cells, which impedes RORγt activity 188 , thus creating another therapeutically exploitable dichotomy between inflammatory and regulatory cells.…”
Section: Gene Expression Regulationmentioning
confidence: 99%
“…Reduced Foxp3 expression was observed in PBMCs from elderly asthmatics [88]. There is an important role for acetylation and deacetylation of Foxp3 in the regulation of this transcription factor [89,90] including on K31, K262 and K267 [91]. It has been identified that p300 and Tip60 can acetylate Foxp3 (intriguingly, p300 and Tip60 work together to acetylate one another and Foxp3) [92].…”
Section: Tregs: Regulation Of the Foxp3 Transcription Factor Acetylatmentioning
confidence: 99%
“…Increased Treg suppressive function (in combination and alone) EX-527 increased acetylation of K31, K262 and K267, and increased the stability and levels of the transcription factor [91,96] Foxp3/Tregs HDAC1-3 inhibitor MS-275 Ambiguous effects [98][99][100] RORγt/Th17 HDAC1-3 inhibitor MS-275 Enhanced Th17 differentiation in mouse splenocytes [106] RORγt/Th17 Pan HDACi givinostat Downregulated the IL-6 receptor on T cells that reduced their ability to differentiate into Th17 cells, but instead skewed differentiation toward the Treg phenotype [107] Foxp3 and RORγt Pan HDACi TSA Increased Foxp3 and decreased RoRγt levels in an ovalbumin challenge asthma mouse model [38] HDAC: Histone deacetylase; HDACi: Histone deacetylase inhibitor; PBMC: Peripheral blood mononuclear cell; TSA: Trichostatin A.…”
Section: Macrophages: Selective Regulation Of the Nf-κb Transcriptionmentioning
confidence: 99%
See 2 more Smart Citations